1996
DOI: 10.1159/000129433
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gallbladder Bile Lithogenicity in Patients after Gastrectomy and Colectomy

Abstract: The differences in lithogenicity of gallbladder bile, biliary lipid composition, cholesterol saturation index (CSI), cholesterol nucleation time (NT), bilirubin, and ionized calcium were compared in patients who had previously undergone gastrectomy or colectomy. The increased CSI and the rapid NT were absent in gastrectomized patients, while colectomy significantly increased the CSI and accelerated the NT. The levels of ionized calcium and unconjugated bilirubin, possibly responsible for pigment stone formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…[1][2][3] The reported reasons for this postoperative disease have included gallbladder physiological change 4 as well as lithogenic change in bile juice. 5 Such changes may be caused by the various surgical procedures involved in vagotomy, 6,7 gastric resection 8 , and intestinal reconstruction. 9,10 Gastric surgery for malignancy now includes a number of options regarding methods for gastric resection, reconstruction, and lymph-node dissection.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The reported reasons for this postoperative disease have included gallbladder physiological change 4 as well as lithogenic change in bile juice. 5 Such changes may be caused by the various surgical procedures involved in vagotomy, 6,7 gastric resection 8 , and intestinal reconstruction. 9,10 Gastric surgery for malignancy now includes a number of options regarding methods for gastric resection, reconstruction, and lymph-node dissection.…”
Section: Introductionmentioning
confidence: 99%
“…Problems related to treatment of Bil.TRs after gastric surgery include the mechanism of the occurrence of these stones, methods for prevention of recurrent stones, the indications for Lap‐C in patients with GBs, and the optimum treatment of CBDs after gastrointestinal reconstruction. Mechanisms underlying the formation of Bil.TRs after gastrectomy are thought to include changes in the composition of bile, the effect of vagotomy, biliary tract infection, gastric resection, intestinal reconstruction and CBD dilatation . A decrease of papillary function and diminished peristalsis of the CBD and GB occur after vagal denervation, while dilation of the CBD and GB is associated with cholestasis after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Performing gastrectomy for benign or malignant disease may increase the incidence of biliary tract stones (Bil.TRs), including gallbladder stones (GBs) and common bile duct stones (CBDs), and these stones occur in about 10–30% of patients after gastrectomy . Development of Bil.TRs is thought to involve multiple mechanisms, including a change in the formation of bile juice, a decrease of biliary tract motility, and altered papilla of Vater activity due to denervation after resection of the vagal nerve .…”
Section: Introductionmentioning
confidence: 99%
“…The increased incidence of cholelithiasis in patients after colectomy has been attributed to increased cholesterol saturation and a rapid nucleation time of gallbladder bile, as a consequence of relatively high biliary content of cholesterol and low content of phospholipids and bile acids [9,10,11]. In two other studies, no increased cholesterol saturation of duodenal bile was observed [12,14], and a recent study, in which gallbladder bile was obtained by direct puncture of the gallbladder, revealed that biliary lipid composition and cholesterol saturation of bile may be normal after colectomy [13].…”
Section: Discussionmentioning
confidence: 99%
“…This has been attributed to an increased loss of bile acids [7,8] followed by an elevated cholesterol saturation and facilitated nucleation of cholesterol in gallbladder bile [9,10,11]. However, some studies in colectomized patients have found normal biliary cholesterol saturation, normal biliary lipid composition and normal nucleation time [12,13,14].…”
Section: Introductionmentioning
confidence: 99%